2011
DOI: 10.4047/jap.2011.3.2.96
|View full text |Cite
|
Sign up to set email alerts
|

Full mouth implant rehabilitation of a patient with ectodermal dysplasia after orthognathic surgery, sinus and ridge augmentation: a clinical report

Abstract: An 18-year-old male presented severe hypodontia due to hypohidrotic ectodermal dysplasia was treated with Le Fort I maxillary osteotomy with simultaneous sinus floor augmentation using the mixture of cortical autogenous bone graft harvested from iliac crest and organic Bio-Oss to position the maxilla in a right occlusal plane with respect to the mandible, and to construct adequate bone volume at posterior maxilla allowing proper implant placement. Due to the poor bone quality at other sites, ridge augmentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 7 publications
(14 reference statements)
0
21
0
Order By: Relevance
“…In the literature, we found several case reports about adult patients with ectodermal dysplasia successfully rehabilitated with this technique. [9][10][11][12][13][14][15][16][17][18][19] Lypka et al, 12 for example, used bilateral sinus lift and block grafting in the maxilla combined with extraoral implant placement and bone grafting ("tent pole" technique) in the mandible to restore the maxillofacial complex. Li et al 15 used onlay grafts in the maxilla and alveolar distraction in the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, we found several case reports about adult patients with ectodermal dysplasia successfully rehabilitated with this technique. [9][10][11][12][13][14][15][16][17][18][19] Lypka et al, 12 for example, used bilateral sinus lift and block grafting in the maxilla combined with extraoral implant placement and bone grafting ("tent pole" technique) in the mandible to restore the maxillofacial complex. Li et al 15 used onlay grafts in the maxilla and alveolar distraction in the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, several authors have reported normal healing and comparable osseointegration rates between ED patients and healthy controls. 3,4,8,9,[11][12][13] Garagiola et al compared osseointegration in ED and non-ED patients followed up to 3 years. Ninety-one percent success rate in ED patients and 95.8% success rate in non-ED patients were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have documented the need for extensive augmentation procedures in ED patients allowing future implant placement. 3,4 This case report presents a multidisciplinary approach to treating oligodontia in a hypohidrotic ED patient.…”
mentioning
confidence: 97%
“…Orthognathic surgery such as Lefort 1 maxillary advancement surgery is indicated in cases of severely retruded chin with abnormal shortness of the lower jaw 1,20 . Double jaw orthognathic surgery combining Lefort 1 osteotomy and correction of the mandibular prognathism by sagittal split according to Epker, can also be performed when dealing with severe phenotypes 20 .…”
Section: B -Different Types Of Surgerymentioning
confidence: 99%
“…Therefore, the first surgical procedure may involve a Lefort 1 osteotomy with maxillary sinus floor lift elevation and autologous bone grafts applied laterally to the cortical bone. After a period of bone healing and engraftment, with a healing time which should be preferably lengthened when dealing with syndromes, the second surgical procedure is the placement of the osteointegrated implants 1 . A combination of single or double jaw orthognathic surgery and placement…”
Section: B -Different Types Of Surgerymentioning
confidence: 99%